2016
DOI: 10.5897/ajar2015.10498
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of agroecology and conventional farming techniques on small-scale peasant farmers crop yields in the Fako and Meme divisions of Cameroon

Abstract: Small-scale farming constitutes a very important segment of the food production chain in most third world countries. In Cameroon for example, they constitute about 70% of the agrarian population. This study aimed at verifying the effects of agroecology and conventional farming techniques on crop yields in four sites in the South West Region of Cameroon from small-scale farms. Data were obtained through the administration of 200 questionnaires and two focus group discussions (FGDs). The data were analyzed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Research in other regions has shown that there are no clear conclusions regarding productivity between CS and NCS. Epule and Bryant [71] and Heilig and Kelly [72] argued that older bean cultivars ( P . vulgaris ) had a lower performance compared to modern commercial cultivars regardless of the production system, although some genotypes showed a better performance under organic production systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in other regions has shown that there are no clear conclusions regarding productivity between CS and NCS. Epule and Bryant [71] and Heilig and Kelly [72] argued that older bean cultivars ( P . vulgaris ) had a lower performance compared to modern commercial cultivars regardless of the production system, although some genotypes showed a better performance under organic production systems.…”
Section: Resultsmentioning
confidence: 99%
“…Productivity can vary across a large number of factors depending on the nature of the crops and species as well as the different environmental conditions, the crop’s conservation status [74], and human behavioral factors. The aforementioned human factors that affect productivity, including more attention paid by agroecological growers to small-scale gardens compared to commercial plots, could also explain differences in productivity and are related to farm size [71, 73].…”
Section: Resultsmentioning
confidence: 99%